Long Distance Interpersonal Communication Patterns of Parents and Children - Tamsil, Ilma Saakinah; Andary, Ria Wuri; Khairunnisak, Khairunnisak (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Well - established family communication will give attachment and mutual need to form communication patterns . For children who live far from their parents, communication is relied on media intermediaries and quite a few experience a lack of communication effective . The urgency of this research is seen long- distance interpersonal communication patterns of parents and children especially for Communication Science students at Medan Area University class of 2022 who come from from outside Medan and its obstacles . This qualitative research method uses Focus Group Discussion which involves ten parents and ten child as a participant. The result is the long- distance interpersonal communication patterns of parents and children use secondary communication patterns that is via cellphone. Characteristics of interpersonal communication can be strengthen interpersonal relationships between parents and children especially in context parenting . Ten parent participants applied authoritative communication patterns , meanwhile authoritarian communication patterns , permissive communication patterns No found. However, communication is established tend to only fulfill material needs and focus more on the mother. The role of fathers is still minimal, what can be done impact on fatherless parenting. Obstacle factor long distance communication patterns viz internet connection , busy parents and children making communication limited. It is important for parents and children to maintain effective communication in order to benefit the not lost because distance physique .